A.I.M. : the powerful 10-step personal and career success program - Carlisle, Jim (J. Wiley & Sons Canada, 2010)
"That is what the A.I.M. method is meant to do-to help people, as individuals, start on the path towards realizing their true potential. By doing this, it can help more people to care, more people to engage, more people to make a difference for themselves and every one around them"--Page 3.